The Effect of Good Agricultural Practices on the Technical Efficiency of Chili Production in Thailand - Wirat Krasachat (Sustainability, 2023)
While recognition of the positive influence of good agricultural practices (GAP) on reducing negative externalities due to conventional farming and providing more export opportunities is growing, there is some doubt about the effects of GAP on the economic performance of chili farms. In this regard, this study’s principal objectives are to assess the impact of GAP and to examine farm-specific and environmental factors regarding the technical efficiency (TE) of chili farms in Thailand. This study employed a stochastic meta-frontier input distance function to measure and explore the effects of farm-specific and environmental factors on TE using 2018 farm-level survey data from Thai chili farms. The sample of 100 farms includes GAP and non-GAP farms. The empirical results highlight three critical findings. First, there is confirmation that GAP positively influence the TE of chili farms. Second, family labor intensity and small farm size also positively impact the TE of farms. At the same time, completion of a technical training course positively affects the TE of non-GAP farms only. Finally, education, experience, training courses, and crop diversification negatively affect the TE of GAP farms only. Thus, policymakers need to focus on GAP adoption and farm-specific factors to promote the sustainable development of Thai chili farms.
Keywords: Efficiency Analysis Using DEA; Irrigation Practices and Water Management; Agricultural Innovations and Practices